Comprehensive land consolidation in China - Yan, Jinming, 1965-; Xia, Fangzhou, 1989- (New York, NY : Routledge, 2023)
"This book systematically investigates the strategy and practice of comprehensive land consolidation in China by assessing the objective of the program and its implementation. In the first part of the book, the authors first review the development and historical policy of land consolidation and land rehabilitation, with a focus on initiatives inaugurated in China since the 1980s. The following three chapters analyze different modes, approaches, and measures of land consolidation. The second part focuses on planning patterns designed and implemented in different territorial and geographical regions in China, including urban and rural areas, ecological function zones, mining areas, and coastal regions and islands. It also looks into the institutional basis, supportive measures, and mechanisms for the coordinated regional implementation of land consolidation at the macro, medium, and micro levels. Based on their findings, the authors advance ten actionable policy suggestions on the promotion of China's land consolidation. The title will appeal to scholars, students, and policy makers interested in economic management, land planning, and natural resources management"--
OCLC-licensed vendor bibliographic record.
Keywords: Consolidation of land holdings -- China; Consolidation of land holdings -- Law and legislation -- China; Land use -- China; Regional planning -- China; BUSINESS & ECONOMICS / Management; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development